Quality of life and social distancing: systematic review of literature (Research, Society and Development, 2020)
The city of Wuhan, capital of China's Hubei province, was the scene of an outbreak of a new coronavirus called the SARS-CoV-2 by the World Health Organization (WHO). Gradually, several countries developed strategies to reduce community contamination, including social isolation and lockdown. The purpose of this study is carry out a systematic review of studies that assessed quality of life in social distance during pandemics. A high sensitivity search was carried out in the main scientific databases associated with quality of life (MEDLINE via PUBMED, Embase, Lilacs, Scielo, PsycoInfo, Pepsic, Scopus e Cochrane Library).  The full-text versions were analyzed for methodological quality by two researchers independently and disagreement between reviewers was resolved by discussion or arbitration by the other researcher. Only cross-sectional studies that assessed health-related quality of life during SARS-CoV, MERS-CoV and SARS-CoV-2 outbreaks were included. Editorial, letter to the editor, point of view, case presentation or brief communication were excluded. 1072 studies were identified, of which 1067 were excluded following the PRISMA protocol, with 5 articles remaining at the end. Patients affected by SARS, MERS and COVID-19 had reduced quality of life and social distancing make it worse.